BAKTERI PATOGEN PADA KEPITING KELAPA (Birgus latro) - Muhammad Aris; Sudirto Malan (JURNAL PERIKANAN TROPIS, 2021)
Coconut crab (Birgus latro) is a fishery resource with high economic value. Coconut Crab is only found in eastern Indonesia, covering Sulawesi, Maluku and North Maluku. One of the habitat of Coconut Crab in North Maluku is Moor Island, Central Halmahera. The coastal typology of this island is predominantly rocky with many gaps and small caves, as well as several steep slopes with dominant vegetation conditions of coconut, beach pandanus and other coastal plants. Walnut Crab is often used as a consumption ingredient because it has delicious taste and high nutritions. However, the use of crustaceans for consumption can also be dangerous. This is because crustaceans also contain several pathogenic bacteria. This study aimed to identify pathogenic bacteria isolated from Coconut Crab which is the largest crustacean in the world. 5 samples of Coconut Crab were taken from Moor Island. Isolated samples marked KK1, KK2, KK3, KK4 and KK5. Pure bacterial isolates were obtained from Coconut Crab samples, evaluated for colony type and identified based on biochemical characterization. The types of pathogenic bacteria identified in samples KK1, KK2, KK3, KK4 and KK5 were Escherichia coli, Pseudomonas sp. and Staphylococcus sp.